Quality Control System of Red Jujube by Hybrid Model: Development of an Efficient Framework - Jing, Rongzhi; Li, Ping (Frontiers in Plant Science, 2022)
Food traceability is very important for the quality and safety of agricultural products, which is related to the people livelihood and national economy and has drawn great attention from governments and scientists around the world. The existing studies have not yet overcome the crisis characteristics comprehensively and systematically. A traceability system of Red Jujube is constructed by hybrid mode of blockchain and Internet of Things (IoT). The system integrates the block chain and IoT technologies with characteristics of tamper-proof, de-centralization and distributed storage, and solves the problem of date quality traceability by designing the technical process and architecture of date quality traceability and the big data of red jujube, jujube plantation, processing enterprise, commercial enterprises and market administration. The whole process from planting to processing and sales of red jujube are recorded in the block to ensure the realization of quality traceability of red dates in the process. Through the whole process of big data processing, the key information collected in each process is stored in the database to ensure the realization of quality traceability of red dates in the framework. The system can help to minimize the production and distribution of unsafe or poor quality products, thereby minimizing the potential for bad publicity, liability, and recalls.